TECHNOPHOBIA IN ACADEMIA: IMPLICATION FOR SUSTAINABLE RESEARCH DEVELOPMENT IN TERTIARY INSTITUTIONS IN NIGERIA - Nebo, Ann N. (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
The contemporary education ecosystem mainly depends on the ever-increasing technological innovations linked to inquiry-based learning development. However, research indicates that lack of technology acceptance fuels the divide in technological integration in the education sector. The study's primary purpose is to examine the prevalence of technophobia and its implication in research development in academia. One hundred and twenty-seven academic staff of three public tertiary institutions in Enugu State, Nigeria, participated in the study. The respondents completed a self-report measure of the computer anxiety rating Scale and research attitudes questionnaire. The descriptive report indicated that most respondents scored high in technophobia (46.5%). Furthermore, the linear regression analysis conducted on the data revealed that technophobia statistically significantly predicted research attitudes in academia F (1,125), 20.31, P<.000. Importantly, the R2 indicated that the predictor variable accounted for 22.1% of the observed variance research attitudes in academia. The result has implications for research development in Nigeria's academia.